Risk of cancer in pre-dialysis chronic kidney disease: A nationwide population-based study with a matched control group - Sehoon Park; Soojin Lee; Yaerim Kim; Yeonhee Lee; Min Woo Kang; Kyungdo Han; Seoung Seok Han; Hajeong Lee; Jung Pyo Lee; Kwon Wook Joo; Chun Soo Lim; Yon Su Kim; et al. (The Korean Society of Nephrology, 2019)
Background : Cancer risk and epidemiology in pre-dialysis chronic kidney disease (CKD) warrant further investigation in a large-scale cohort. Methods : We performed a nationwide population-based study using the national health insurance database of Korea. We screened records from 18,936,885 individuals who received a national health examination ≥ 2 times from 2009 to 2016. Pre-dialysis CKD was identified based on serum creatinine and dipstick albuminuria results. Individuals with preexisting cancer history, renal replacement therapy, or transient CKD were excluded. A control group without evidence of kidney function impairment and matched for age, sex, low-income status, and smoking history was included. Risk of cancers, as identified in the claims database, was investigated using a multivariable Cox regression model including matched variables and other unmatched clinical characteristics as covariates. Results : A total of 471,758 people with pre-dialysis CKD and the same number of matched controls were included. Urinary (adjusted hazard ratio [HR], 1.97; 95% confidence interval [95% CI], 1.82-2.13) and hematopoietic (adjusted HR, 1.53; 95% CI, 1.38-1.68) malignancy risk was increased in pre-dialysis CKD and all CKD stages. However, the risk of digestive cancer was lower in the pre-dialysis CKD group (adjusted HR, 0.89; 95% CI, 0.87-0.92). The risk of digestive, respiratory, thyroid, and prostate malignancy demonstrated a non-linear association with CKD stage, with stage 1 or stage 4/5 CKD without dialysis demonstrating relatively lower risk. Conclusion : Cancer risk varied in pre-dialysis CKD compared to controls, and the association between cancer risk and CKD stage varied depending on the cancer type.